Disease-modifying effects of COX-2 selective inhibitors and non-selective NSAIDs in osteoarthritis: a systematic review. Issue 10 (October 2018) - Nakata, K.; Hanai, T.; Take, Y.; Osada, T.; Tsuchiya, T.; Shima, D.; Fujimoto, Y.
Summary: Osteoarthritis (OA) is a potentially disabling disease whose progression is dependent on several risk factors. OA management usually involves the use of non-steroidal anti-inflammatory drugs (NSAIDs) that are the primary pharmacological treatments of choice. However, NSAIDs have often been associated with unwanted side effects. Cyclooxygenase (COX)-2 specific inhibitors, such as celecoxib, have been successfully used as an alternative in the past for OA treatment and have demonstrated fewer side effects. While abundant data are available for the clinical efficacy of drugs used for OA treatment, little is known about the disease-modifying effects of these agents. A previous review published by Zweers et al. (2010) assessed the available literature between 1990 and 2010 on the disease-modifying effects of celecoxib. In the present review, we aimed to update the existing evidence and identify evolving concepts relating to the disease-modifying effects of not just celecoxib, but also other NSAIDs. We conducted a review of the literature published from 2010 to 2016 dealing with the effects, especially disease-modifying effects, of NSAIDs on cartilage, synovium, and bone in OA patients. Our results show that celecoxib was the most commonly used drug in papers that presented data on disease-modifying effects of NSAIDs. Further, these effects appeared to be mediated through the regulation of prostaglandins, cytokines, and direct changes to tissues. Additional studies should be carried out to assess the disease-modifying properties of NSAIDs in greater detail.